Stereotypic behaviour in standard non-enriched cages is an alternative to depression-like responses in C57BL/6 mice - Fureix, Carole; Walker, Michael; Harper, Laura; Reynolds, Kathryn; Saldivia-Woo, Amanda; Mason, Georgia (Behavioural brain research, 2016)
•We compared home-cage and Porsolt test behaviour in enriched and non-enriched mice.•Non-enriched mice spent more time still but awake in the home cage..•High levels of still but awake predicted longer float times.•Non-enriched mice were also more stereotypic.•Being stereotypic and spending time still but awake were inversely correlated. Depressive-like forms of waking inactivity have been recently observed in laboratory primates and horses. We tested the hypotheses that being awake but motionless within the home-cage is a depression-like symptom in mice, and that in impoverished housing, it represents an alternative response to stereotypic behaviour. We raised C57BL/6 (‘C57’) and DBA/2 (‘DBA’) females to adulthood in non-enriched (n=62 mice) or enriched (n=60 mice) cages, observing home-cage behaviour during the active (dark) phases. We predicted that being still but awake would be reduced by environmental enrichment; more pronounced in C57s, as the strain most prone to learned helplessness; negatively related to stereotypic behaviour; and positively related to immobility in Forced Swim Tests (FST). Compared to enriched mice, non-enriched subjects did spend more time spent being inactive but awake, especially if they displayed relatively little stereotypic behaviour. C57 mice also spent more time awake but motionless than DBAs. Furthermore, even after statistically controlling for housing type and strain, this behaviour very strongly tended to predict increased immobility in the FST, while high levels of stereotypic behaviours in contrast predicted low immobility in the FST. Being awake but motionless is thus a reaction to non-enriched housing that seems to be an alternative to stereotypic behaviour, and could reflect depression-like states.